Stochastic orders and measures of skewness and dispersion based on expectiles - Andreas Eberl; Bernhard Klar (Statistical Papers, 2022)
Recently, expectile-based measures of skewness akin to well-known quantile-based skewness measures have been introduced, and it has been shown that these measures possess quite promising properties (Eberl and Klar in Comput Stat Data Anal 146:106939, 2020; Scand J Stat, 2021, https://doi.org/10.1111/sjos.12518 ). However, it remained unanswered whether they preserve the convex transformation order of van Zwet, which is sometimes seen as a basic requirement for a measure of skewness. It is one of the aims of the present work to answer this question in the affirmative. These measures of skewness are scaled using interexpectile distances. We introduce orders of variability based on these quantities and show that the so-called weak expectile dispersive order is equivalent to the dilation order. Further, we analyze the statistical properties of empirical interexpectile ranges in some detail.
Keywords: 510; Expectile; Skewness; Stop-loss transform; Dispersion order; Dilation order; Dispersive order; Scale measure; Asymptotic relative efficiency